2019
DOI: 10.3390/biom10010028
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Growth of TSC2-Null Cells by a PI3K/mTOR Inhibitor but Not by a Selective MNK1/2 Inhibitor

Abstract: Lymphangioleiomyomatosis (LAM) is a rare metastatic cystic lung disease due to a mutation in a TSC tumor suppressor, resulting in hyperactive mTOR growth pathways. Sirolimus (rapamycin), an allosteric mTORC1 inhibitor, is a therapeutic option for women with LAM but it only maintains lung volume during treatment and does not provide benefit for all LAM patients. The two major mTORC1 protein synthesis pathways are via S6K/S6 or 4E-BP/eIF4E activation. We aimed to investigate rapamycin in combination with compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…This data supports observations that multi-kinase inhibitors are able to block tumor cell growth and tumor associated angiogenesis simultaneously improving patient outcome and survival. Sorafenib is an FDA-approved multikinase inhibitor (37)(38)(39) that is known to inhibit RAF/MEK/ERK signalling, leading to increased tumor cell apoptosis, decreased micro-vessel density, and decreased metastatic shedding of tumor cells (37)(38)(39)(40) and inhibit the phosphorylation of eIF4E, eukaryotic translation initiation factor, which is upregulated in LAM, downstream of mTOR (3,(39)(40)(41). Our data supports the potential for the use of multikinase inhibitors as a therapeutic option in LAM.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This data supports observations that multi-kinase inhibitors are able to block tumor cell growth and tumor associated angiogenesis simultaneously improving patient outcome and survival. Sorafenib is an FDA-approved multikinase inhibitor (37)(38)(39) that is known to inhibit RAF/MEK/ERK signalling, leading to increased tumor cell apoptosis, decreased micro-vessel density, and decreased metastatic shedding of tumor cells (37)(38)(39)(40) and inhibit the phosphorylation of eIF4E, eukaryotic translation initiation factor, which is upregulated in LAM, downstream of mTOR (3,(39)(40)(41). Our data supports the potential for the use of multikinase inhibitors as a therapeutic option in LAM.…”
Section: Discussionsupporting
confidence: 78%
“…Sorafenib, an FDA-approved multi-kinase inhibitor, inhibits multiple pathways in the tumor microenvironment and has been shown to improve patient outcomes by decreasing tumor cell growth, tumor-associated-angiogenesis, and metastasis (37)(38)(39). Sorafenib also has potential therapeutic benefits by inhibiting eIF4E, eukaryotic translation initiation factor, which is upregulated in LAM downstream of mTOR activation and blocking VEGFR-2 and VEGFR-3 to prevent LAM-associated lymphangiogenesis (3,(39)(40)(41).…”
Section: Introductionmentioning
confidence: 99%
“…However, in a study of 30 LAM lung biopsies, the distribution of p4E-BP1 versus pS6K1 and pS6 demonstrated that there was high expression of all three phosphorylated proteins in LAM bronchi and lung parenchyma [ 29 ]. In four LAM lung fibroblast lines grown in vitro , we showed that pS6, but not p4E-BP1 Thr37/46 , was potently inhibited by 10 nM rapamycin [ 30 ]. In contrast, the dual PI3K/mTOR kinase inhibitor omipalisib inhibited both axes, albeit much more potently (∼100-fold) for pS6 than p4E-BP1 [ 30 ].…”
Section: Mtorc1 Translation Pathways In Lammentioning
confidence: 99%
“…In four LAM lung fibroblast lines grown in vitro , we showed that pS6, but not p4E-BP1 Thr37/46 , was potently inhibited by 10 nM rapamycin [ 30 ]. In contrast, the dual PI3K/mTOR kinase inhibitor omipalisib inhibited both axes, albeit much more potently (∼100-fold) for pS6 than p4E-BP1 [ 30 ].…”
Section: Mtorc1 Translation Pathways In Lammentioning
confidence: 99%
“…An example of a promising PI3K/mTOR inhibitor with phase 1 clinical data in idiopathic pulmonary fibrosis is GSK2126458 (omipalisib) [ 53 ]. In preclinical in vitro studies in Tsc2 -null cells, we showed that omipalisib inhibited phosphorylation of Akt and both protein synthesis arms downstream of mTORC1 activation, namely S6K and 4EBP1 [ 54 ]. It is not widely appreciated that rapamycin, and other allosteric rapalogs, inhibit phosphorylation of S6K at much lower concentrations than they inhibit phosphorylation of 4E-BP1 [ 55 ].…”
Section: Mtor Pathway Inhibitorsmentioning
confidence: 99%